Informatics- AF172- 202200 - Raicovi Nazal, Giancarlo Martin (2022)
Description: This is a conjoint syllabus to fulfill the requirement of two pre requisite courses (MIS11 and MIS112) for those UPC students applying to the University of Arizona BSBA program. Its composed of two parts: Part 1 - MIS 112 (4 lab hours per week, 1 credit hour) Spreadsheet software such as Excel is among the most widespread business tools. People in companies use spreadsheets for a variety of tasks. Some examples include the creation of budgets, information analysis, financial analysis, creation of charts, and organization of lists/tables. They also serve as front-end for large corporate databases. Purpose: Aims to help students understand how to use spreadsheets and develop a sense of the effective use of this technology to solve business tasks. This course introduces them to many aspects of Excel. The concepts they learn can be applied to spreadsheet software within several office productivity packages. Part 2 - MIS 111 (6 theory hours per week, 3 credit hour) Introduces the information-driven methods used by business, society, and individuals to understand complex problems and make informed decisions. In this class, you will develop skills related to critical thinking, quantitative analysis and qualitative assessment that will provide you with the foundation for the effective and 1ethical use of information and technology. The course is built around three central themes: The Organization of Information, Analysis and Decision- making Strategies, and Technologies for Communication and Collaboration. The first theme, Organization of Information, considers how information systems are used to organize data in a business environment. How does an organization manage and access its information about its processes, products, customers and vendors in order to use it effectively? We will learn about the structure of information, the application software businesses use to manage information, and environments where information systems add value. The second theme is Analysis and Decision-making Strategies. Once an organization¿s information is in an organized and manageable structure, how do individuals within a business use and analyze the information and make decisions? We¿ll learn how data analysis tools find patterns and trends in our data that give businesses a strategic advantage in the marketplace. The final theme is Technologies for Communication and Collaboration. How do businesses use information technology to create sustainable strategic value? We¿ll look at technologies that help businesses collaborate and manage projects as well as communicate with their customers, such as social media, project management and web development applications.